La2O3 Nanoparticles Induce Reproductive Toxicity Mediated by the Nrf-2/ARE Signaling Pathway in Kunming Mice - Yuan L (Dove Medical Press, 2020)
Lu Yuan,1 Qingzhao Li,1 Disi Bai,2 Xueliang Shang,2 Fen Hu,3 Zhenfei Chen,4 Tianyang An,5 Yajing Chen,6 Xiujun Zhang1 1College of Public Health; 2College of Psychology; 3College of Life Sciences; 4Environmental Monitoring Center Tang Shan, Tangshan 063210, Hebei, People’s Republic of China; 5College of Ji Tang; 6College of Pharmacy of North China University of Science and Technology, Tangshan 063210, Hebei, People’s Republic of ChinaCorrespondence: Xiujun ZhangNorth China University of Science and Technology, Bohai Avenue 21, Tangshan 063210, Hebei, People’s Republic of ChinaTel +86-315-3726335Fax +86-315-3726341Email xiujunzhang66@126.comDisi BaiCollege of Psychology, North China University of Science and Technology, Bohai Avenue 21, Tangshan 063000, People’s Republic of ChinaEmail baidisi@163.comPurpose: Lanthanum oxide (La2O3) nanoparticles (NPs) have been widely used in catalytic and photoelectric applications, but the reproductive toxicity is still unclear. This study evaluated the reproductive toxicity of two different-sized La2O3 particles in the testes.Materials and Methods: Fifty Kunming mice were randomly divided into five groups. Mice were treated with La2O3 NPs by repeated intragastric administration for 90 days (control, nano-sized with 5, 10, 50 mg/kg BW and micro-sized with 50 mg/kg BW). Mice in the control group were treated with de-ionised water without La2O3 NPs. Sperm parameters, testicular histopathology, TEM assessment, hormone assay and nuclear factor erythroid 2-related factor 2 (Nrf-2) pathway were performed and evaluated.Results: The body weight of mice treated with La2O3 NPs or not had no difference; sperm parameters and histological assessment showed that La2O3 NPs could induce reproductive toxicity in the testicle. Serum testosterone and gonadotropin-releasing hormone (GnRH) in the NH (nano-sized with 50 mg/kg BW) group were markedly decreased relative to control group, and an increase of luteinizing hormone (LH) in NH group was detected . Additionally, transmission electron microscopy revealed that the ultrastructural abnormalities induced by La2O3 NPs were more severe than La2O3 MPs in the testes. Furthermore, La2O3 NPs treatment inhibited the translocation of nuclear factor erythroid 2-related factor 2 (Nrf-2) from the cytoplasm into the nucleus as well as the expression of downstream genes NAD(P)H quinone oxidoreductase1 (NQO1), hemeoxygenase 1 (HO-1) and (glutathione peroxidase) GSH-Px, thus abrogating Nrf-2-mediated defense mechanisms against oxidative stress.Conclusions: The results of this study demonstrated that La2O3 NPs improved the spermatogenesis defects in mice. La2O3 NPs inhibited Nrf-2/ARE signaling pathway that resulted in apoptosis in the mice testes.Keywords: La2O3 nanoparticles, reproductive toxicity, inflammation, Nrf-2/ARE signaling pathway, apoptosis